Supply chain optimization under risk and uncertainty: A case study for high-end server manufacturing. (March 2016) - Aqlan, Faisal; Lam, Sarah S.
Highlights: We propose an approach for supply chain optimization under risk and uncertainty. Simulation and optimization models are combined through an iterative procedure. A software application is developed based on the proposed approach. To validate the proposed approach, a case study is provided. Abstract: This paper presents an approach and a software application for supply chain optimization under risk and uncertainty. The proposed approach combines simulation and optimization techniques for managing risks in supply chains. A multi-objective optimization model is developed which considers the deterministic features of the supply chain. A simulation model is used to represent the stochastic features of the supply chain. Both models communicate to achieve the best values for profit, lead time and risk reduction by selecting a combination of mitigation strategies and allocating orders and inventory. A case study from a high-end server manufacturing environment is used to demonstrate the validity of the proposed approach. The analytical results show clear trade-offs among the three objectives where changing the risk reduction goal value will affect the total profit and lead time. The proposed approach helps decision makers identify the best risk mitigation strategies and allocate inventory and customer orders effectively.